THE DEPRESSION SYMPTOMS OF THE CHARACTER NIC SHEFF IN THE FILM BEAUTIFUL BOY BY FELIX VAN GROENINGEN. - Aziz, Nazwa Aliya (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2023)
The title of this research is Depression Symptoms of Nic Sheff in Beautiful Boy by Felix Van Groeningen. The research aims to find out the symptoms of Nic Sheff's depression in the film Beautiful Boy by Felix Van Groeningen. The problem in this study focused on the symptoms of depression of Nic's character, which analyzes the symptoms of depression through 6 aspects of depression according to Beck and Alford. The method used in this research is descriptive qualitative method in which presents the data in descriptive form. The approach used is a literary psychology approach while researchers use reading and note-taking techniques as data collection techniques. The data in this study used are dialog and scene cuts derived from primary data sources, namely the film Beautiful Boy by Felix Van Groeningen. Secondary data sources are obtained from reference books or documents related to the object of research. The data collection technique used is to collect data using reading and note-taking techniques. Based on the final results of the research conducted on the film Beautiful Boy shows that Nic there are symptoms of depression faced by the main character, namely emotional aspects, cognitive aspects, motivational aspects, physical aspects, delusions, and hallucinations.